Ligand free, highly efficient synthesis of diaryl ether over copper fluorapatite as heterogeneous reusable catalyst - Mulla, Shafeek Abdul Rashid; Inamdar, Suleman M.; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (Tetrahedron Letters, 2012)
A novel ligand-free, highly efficient, and an inexpensive method has been developed by using ecofriendly, heterogeneous reusable copper fluorapatite (CuFAP) catalyst for the synthesis of diaryl ethers from the cross coupling reaction of the various substituted aryl halides (fluoride, chloride, bromide, and iodide) with the potassium salts of various substituted phenols in the presence of N-methyl 2-pyrrolidone (NMP) as a solvent at 120 degrees C. The protocol obtained the corresponding cross coupling products in good to excellent yield. The CuFAP catalyst was recovered by simple filtration from the reaction mixture and reused several times without the loss of catalytic activity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arylhalide; Copper fluorapatite; Diaryl ethers; phenol; Ullmann coupling

Ligand-, base-, co-catalyst-free copper fluorapatite (CuFAP) as a versatile, ecofriendly, heterogeneous and reusable catalyst for an efficient homocoupling of arylboronic acid at ambient reaction conditions - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Shaikh, Taufeekaslam M. Y. (RSC Advances, 2015)
This paper describes the first report in which copper species containing copper fluorapatite (CuFAP) acts as a versatile, eco-friendly, recyclable, heterogeneous catalyst for an efficient synthesis of symmetric biaryls from the homo-coupling of arylboronic acids in methanol solvent at ambient reaction conditions. The developed protocol is ligand-, base-, and co-catalyst-free, sustainable, mild, inexpensive, and compatible with a wide range of aromatic/heterocyclic boronic acids and provides the corresponding products in excellent yields without purification. The catalyst was easily recovered from the reaction mixture and reused several times without loss of activity.